Relationship between sleep disorders and attention-deficit–hyperactivity disorder in children - Yin, Huimei; Yang, Dong; Yang, Lin; Wu, Guangsheng (Frontiers in Pediatrics, 2022)
Objective: To explore the correlation between sleep disorders and attention-deficit–hyperactivity disorder (ADHD) in children. Methods: We studied 100 Chinese children (70 boys and 30 girls; mean age, 8.77 ± 2.39 years). Parents completed the Children's Sleep Disturbance Scale (SDSC) and the Swanson Nolan and Pelham Version IV Scale (SNAP-IV) questionnaires. SNAP-IV and SDSC scores were compared in children with and without sleep disorders and ADHD. Results: There were significant differences in SDSC scores, Arousal Disorder (AD) scores, and Sleep Breathing Disorder (SBD) scores between children with and without ADHD (P < 0.05). The sleep disorder group had higher SNAP-IV scores than the non-sleep disorder group (P < 0.05). Children with sleep disorders showed higher ADHD symptom values (inattention, hyperactivity/impulsivity, and oppositional defiance) than children without sleep disorders (P < 0.01). There was a moderate correlation between SDSC scores and SNAP-IV scores (r = 0.486, P < 0.05). Using SNAP-IV scores as the dependent variable, multiple linear regression analysis was applied, and a statistically significant effect of AD and Sleep–Wake Transition Disorder (SWTD) scores on SNAP-IV scores was found (P < 0.05). The area under the curve (95% CI) of the SDSC score for predicting sleep disorders with ADHD was 0.714 (0.606, 0.821; P = 0.0005). Conclusion: Children with ADHD are prone to sleep disorders. The higher the ADHD symptom score, the more sleeping problems. Sleep disorders can also cause or exacerbate ADHD symptoms, and the ADHD symptom score correlates with sleep disorder severity. We can reduce the severity of attention-deficit–hyperactivity in children with ADHD by improving their sleep with behavioral sleep interventions.